Development of an RPA-CRISPR/LbaCas12a-Lateral Flow Assay for the Visual Detection of Chrysotila dentata (Haptophyta) - Jiating Yu; Yun Shen; Qinfei Zhang; Xuxu Luo; Yujie Zong; Chengxu Zhou; Hailong Huang; Haibo Jiang (Microorganisms, 2025)
Chrysotila dentata (Haptophyta), a harmful algal bloom (HAB) species frequently occurring in coastal waters of China, is one with strong environmental adaptability that poses a serious threat to marine ecosystems and fisheries. Current molecular detection techniques and early warning systems for this species remain limited. To address this, we developed a rapid and highly sensitive detection method for C. dentata. This method integrates recombinase polymerase amplification (RPA) with CRISPR-LbaCas12a and lateral flow dipstick (LFD) technologies, enabling visual readout of results. Key parameters, including the single-stranded DNA (ssDNA) reporter concentration, reaction time, and temperature, were systematically optimized. Field water sample testing demonstrated high specificity and sensitivity, achieving a detection limit of 5 × 10−6 pg μL−1 for genomic DNA under laboratory conditions and 2.82 × 101 cells mL−1 in simulated environmental samples. The entire detection process takes only 1 h (at a constant 39 °C), and results can be directly interpreted via LFD strips. For early warning and prevention of C. dentata outbreaks, this assay provides a powerful, reliable, and field-ready monitoring tool.